Effects of Blended Biodiesel Coupled with Miller Cycle on Combustion and Emissions of Marine Diesel Engines. Issue 1 (1st January 2023) - Zhang, Feifei; Lin, Hang; Wang, Qiwei; Chen, Jian; Ye, Zixiao; Fan, Jinyu; Li, Pinfang; Huang, Jialiang
Abstract: In order to study the effect of blended biodiesel coupled Miller cycle technology on the combustion and emission performance of diesel engine, the 4190 diesel engine was simulated by AVL-FIRE software. The Miller degree and different blending ratios of biodiesel are simulated and analyzed. The results show that: under the same Miller degree, with the increase of the blending ratio, the explosion pressure decreases significantly, the cylinder temperature decreases, the CO emission decreases significantly, and the NO emission increases. Soot emissions have dropped significantly. Under the same blending ratio, with the increase of Miller degree, the explosion pressure increases, the cylinder temperature decreases gradually but not obviously, the CO emission decreases, the NO emission increases first and then decreases, and the Soot emission decreases. Therefore, selecting the appropriate blending ratio and Miller degree can better reduce NO emissions, and at the same time have a better inhibitory effect on the generation of Soot and CO, and the power performance of the diesel engine is slightly improved. The results of this study provide a solution for the practical application of biodiesel.